2017
DOI: 10.1021/acs.joc.7b01570
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Heck Reaction as a Tool for Para-selective Olefination of Aniline: A DFT Supported Mechanism

Abstract: This study describes the first para-selective palladium-catalyzed alkenylation of tertiary amines. This regioselective C-H activation was conducted without any chelation moieties. A series of olefins were reacted under mild reaction conditions at 60 °C, and the corresponding products were obtained in good yields with high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The IC 50 values were obtained from dose–response curves. In the second method, the IC 50 values were determined with QSAR method. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The IC 50 values were obtained from dose–response curves. In the second method, the IC 50 values were determined with QSAR method. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…In 2017, Karimi and co-workers demonstrated the paraselective alkenylation of anilines under mild conditions using Pd(OAc) 2 and Cu(OAc) 2 (Scheme 31). 59 The presence of AcOH was crucial in maintaining the acidic conditions to diminish the strong binding of the nitrogen atom of aniline to the Pd(II) ion. Both terminal and internal alkenes were suitable for this transformation.…”
Section: Scheme 30 Aerobic Direct Olefination Of Anilines and Arenes mentioning
confidence: 99%
“…In 2009, Mao et al. reported samarium powder catalyzed Sonogashira reaction . The important features of Sm are being stable in air, cheap and easy to handle.…”
Section: Introductionmentioning
confidence: 99%
“…[26] In 2009, Mao et al reported samarium powder catalyzed Sonogashira reaction. [27] The important features of Sm are being stable in air, cheap and easy to handle. From the viewpoint of safety and economy and in continuation of our…”
Section: Introductionmentioning
confidence: 99%